Pengendalian Kualitas dengan Menggunakan Metode Six Sigma dan Multivariate Exponentially Weighted Moving Average (MEWMA) pada Produk EQ Spacing di PT Sinar Semesta - Alvito Shultan Alfiansyah; Elly Wuryaningtyas Yunitasari; Kusmendar Kusmendar (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
In the production process of EQ Spacing products at PT Sinar Semesta, it was discovered that there were eight types of defects which resulted in product defects exceeding company standards. The aim of this research is to carry out a series of analyzes and actions focused on controlling product quality and identifying various aspects that require improvement during the production process. The types of defects with the highest percentage include uneven surfaces at 35.3%, porous at 24.9%, and chipped at 19.3%. Using the Multivariate Exponentially Weighted Moving Average (MEWMA) approach with a weight of 4.05, shifts were found in periods 6, 10, 11, 12, 13, 14, and 15 of the MEWMA graph, with a DPMO value of 24268 and a sigma of 3.5. This analysis demonstrates that in order to prevent excessive defects, production process performance must be improved. PT Sinar Semesta must suggest modifications based on the 5W+1H approach in order to lower the quantity of flaws in bag products. The goal of this quality improvement is to get closer to zero defects and a very low failure rate. It is intended that by doing this, the final product will be superior and satisfy the company's quality requirements.